Minamata as Negative Heritage in Modern Japan: Implications for Fukushima - Aoyama, Mami; Hudson, Mark J. (Pacific Geographies, 2013)
This paper examines the industrial pollution that led to mercury poisoning around Minamata Bay in Kuma-moto Prefecture, Japan from the 1950s. It is argued that the social and political ‘lessons’ of Minamata constitute a type of ‘negative heritage’ that presents a microcosm of many of the problems associated with modernity in Japan. Similarities between Minamata and the 2011 Fukushima nuclear accident are discussed and some reasons why the negative heritage of Minamata was ignored at Fukushima are briefly considered.